Real time monitoring for the most vulnerable: pre-primary education in Bangladesh - Akhter, Mahmuda; Chaudhuri, Jay (© 2013 Institute of Development Studies, 2016)
This article was published in the IDS Bulletin [© 2013 Institute of Development Studies] and the definite version is available at : http://doi.org/10.1111/1759-5436.12020. The Journal's website is at: http://onlinelibrary.wiley.com/doi/10.1111/1759-5436.12020/abstract